Pengembangan Media Job Sheet Pembuatan Pola Celana Wanita pada Mata Pelajaran Busana Custom made Kelas IX SMK Negeri Jabon - Cahya Rahmawati Dwi Wulandari; Irma Russanti (Departement of Mathematics Education, 2023)
According to the results of this study was to determine the feasibility of job sheet media and learning outcomes after using the job sheet on the basic competence of making women's pants patterns for class IX custom made clothing at SMK Negeri 1 Jabon. This study used a Research and Development (R&D) approach which was carried out through several stages of development with a one shot case study as a research plan. The research subjects were class XI TB 2 at SMK Negeri 1 Jabon. Data collection techniques use validation sheets and product assessment observation sheets. The results showed that: the subject matter expert validator score obtained a percentage of 100%, the language expert validator score obtained a percentage of 83.3%. the media expert validator score obtained a percentage of 88.2%. The average validation value for all job sheet media is 90.5%, thus the feasibility of the job sheet media being developed is stated to be very feasible (SL). The completeness of student learning is declared complete if it reaches a KKM score of 75, the average student completeness score has a score of 90.5% so that the completeness of learning outcomes after using the media job sheet on average is declared complete.